2010
DOI: 10.1016/j.jmb.2010.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Packaging of FIV Genomic RNA Depends upon a Conserved Long-range Interaction and a Palindromic Sequence within gag

Abstract: The feline immunodeficiency virus (FIV) is a lentivirus that is related to human immunodeficiency virus (HIV), causing a similar pathology in cats. It is a potential small animal model for AIDS and the FIV-based vectors are also being pursued for human gene therapy. Previous studies have mapped the FIV packaging signal (ψ) to two or more discontinuous regions within the 5′ 511 nt of the genomic RNA and structural analyses have determined its secondary structure. The 5′ and 3′ sequences within ψ region interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 62 publications
3
46
0
Order By: Relevance
“…Several riboswitch models have been proposed for HIV-1 [5053], and in the case of FIV, the existence of dual structures has been validated by SHAPE and RNA dimerization assays [54]. Flexibility in retroviral gRNA is created via long-range interactions that have now been observed in several retroviruses, from HIV-1, FIV, MLV, to MPMV and MMTV [6,25,26,33,5559]. The DIS in one conformation is occluded by base pairing and not available for dimerization, thus earmarking this RNA for translation, while the DIS in the other conformation is available as an apical loop on a stem loop, thus allowing dimerization and packaging of the dimeric RNA [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several riboswitch models have been proposed for HIV-1 [5053], and in the case of FIV, the existence of dual structures has been validated by SHAPE and RNA dimerization assays [54]. Flexibility in retroviral gRNA is created via long-range interactions that have now been observed in several retroviruses, from HIV-1, FIV, MLV, to MPMV and MMTV [6,25,26,33,5559]. The DIS in one conformation is occluded by base pairing and not available for dimerization, thus earmarking this RNA for translation, while the DIS in the other conformation is available as an apical loop on a stem loop, thus allowing dimerization and packaging of the dimeric RNA [54].…”
Section: Discussionmentioning
confidence: 99%
“…Following transfection, cultured cells were fractionated into nuclear and cytoplasmic fractions, as described previously [24,25,32,57,59,62,63]. Briefly, packaged viral RNA from the pelleted viral particles and cellular RNAs from the cytoplasmic fractions were isolated using Trizol and Trizol LS reagents (Invitrogen), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the fact that there are substantial sequence heterogeneities among human, simian, and feline lentiviruses, the preservation of such LRIs in these lentiviruses suggest they play important function(s) in the retroviral life cycle (Paillart et al 2002;Kenyon et al 2008Kenyon et al , 2011. A pivotal role of LRIs is further evidenced by the fact that mutations that destabilize these interactions affect several important steps in the retroviral life cycle, including RNA packaging and dimerization (Paillart et al 2002;Abbink and Berkhout 2003;Song et al 2008;Rizvi et al 2010;Lu et al 2011). Similarly, an earlier study on MPMV has shown the importance of gag sequences (involved in maintaining U5-gag LRIs) in RNA packaging, further arguing in favor of the existence of LRIs in vivo and their functional role in the MPMV life cycle (Schmidt et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Nucleocytoplasmic fractionation, virion and RNA isolation, and cDNA preparation Transfected cells were fractionated into cytoplasmic and nuclear fractions and RNA extracted as described earlier (Mustafa et al 2005;Ghazawi et al 2006;Jaballah et al 2010;Rizvi et al 2010). Packaged viral RNAs were prepared from clarified supernatants from transfected cultures after filtration through 0.2 µm filters as described previously (Mustafa et al 2005;Ghazawi et al 2006;Jaballah et al 2010;Rizvi et al 2010).…”
Section: Plasmid Constructionmentioning
confidence: 99%
See 1 more Smart Citation